Dioxin Disrupts Thyroid Hormone and Glucocorticoid Induction of klf9, a Master Regulator of Frog Metamorphosis. (16th February 2022) - Han, David T; Zhao, Weichen; Powell, Wade H
Abstract: Frog metamorphosis, the development of an air-breathing froglet from an aquatic tadpole, is controlled by thyroid hormone (TH) and glucocorticoids (GC). Metamorphosis is susceptible to disruption by 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD), an aryl hydrocarbon receptor (AHR) agonist. Krüppel-like factor 9 ( klf9 ), an immediate early gene in the endocrine-controlled cascade of expression changes governing metamorphosis, can be synergistically induced by both hormones. This process is mediated by an upstream enhancer cluster, the klf9 synergy module (KSM). klf9 is also an AHR target. We measured klf9 mRNA following exposures to triiodothyronine (T3), corticosterone (CORT), and TCDD in the Xenopus laevis cell line XLK-WG. klf9 was induced 6-fold by 50 nM T3, 4-fold by 100 nM CORT, and 3-fold by 175 nM TCDD. Cotreatments of CORT and TCDD or T3 and TCDD induced klf9 7- and 11-fold, respectively, whereas treatment with all 3 agents induced a 15-fold increase. Transactivation assays examined enhancers from the Xenopus tropicalis klf9 upstream region. KSM-containing segments mediated a strong T3 response and a larger T3/CORT response, whereas induction by TCDD was mediated by a region ∼1 kb farther upstream containing 5 AHR response elements (AHREs). This region also supported a CORT response in the absence of readily identifiable GC responsive elements, suggesting mediation by protein-protein interactions. A functional AHRE cluster is positionally conserved in the human genome, and klf9 was induced by TCDD and TH in HepG2 cells. These results indicate that AHR binding to upstream AHREs represents an early key event in TCDD's disruption of endocrine-regulated klf9 expression and metamorphosis.